Efficient Protocol to Discriminate Multiple Ballistic Targets - Min Kim; Sewon Yoon; Inoh Choi; Jooho Jung; Sanghong Park (IEEE Access, 2025)
In this paper, we propose a novel protocol for discriminating multiple ballistic targets during the midcourse and terminal phases of their trajectories. The midcourse-phase protocol includes the following steps: 1) estimating the number of targets, 2) separating the trajectories, and 3) performing discrimination using either a convolutional neural network (CNN) or a nearest-neighbor classifier. The terminal-phase protocol performs discrimination using trajectory information or a CNN. Simulations that consider radar signals calculated using physical optics, indicate that the proposed protocol effectively discriminates between warheads and decoys in scenarios that involve multiple targets.